Study and Deployment of an Automatic Water Consumption Recording System in The Democratic Republic of Congo/Kananga (British Journal of Multidisciplinary and Advanced Studies, 2024)
This article aims to present the different steps required to deploy and configure the proposed solution to monitor and control water consumption in the city of Kananga.Based on the analysis of needs and the constraints of mutual control of water consumption, we will discuss the configuration of the Arduino card and the mechanisms for transmitting data by SMS that we will use to allow REGIDESO subscribers to receive information on their water consumption.